PENGARUH SERVICESCAPE DAN KUALITAS KOMUNIKASI KARYAWAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH BANK MANDIRI DI SURABAYA - Musriha Musriha (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The purpose of this study was to examine direct and indirect effects of an integrated model of servicescape and personal communication quality upon customer loyalty, and considered customer satisfaction as intervening variable. This study used a causal design. The main data used in this study are primary data collected through the circulation of questionnaires to the respondents Mandiri bank customers in Surabaya. The sampling technique using purposive sampling method to determine the sample based on the consideration of researchers. Data Analysis used SEM (Structural Equation Modeling) analysis technique by program package AMOS 16. Based on the analysis it can be concluded that: the result of study supports the influence of servicescape to customer satisfaction, supports the influence of servicescape to customer loyalty, supports the influence of personal communication quality to customer satisfaction, supports the influence of personal communication quality to customer loyalty, supports the influence of customer satisfaction to customer loyalty, supports the influence of servicescape and personal communication quality to customer loyalty through customer satisfaction.